Left ventricular diastolic dysfunction in patients with heart failure with mildly reduced ejection fraction - Abel, Noah; Schupp, Tobias; Schmitt, Alexander; Reinhardt, Marielen; Lau, Felix; Weidner, Kathrin; Ayoub, Mohamed; Mashayekhi, Kambis; Akın, Ibrahim; Behnes, Michael (International journal of cardiology, 2024)
Objective - This study investigates the prevalence and prognostic impact of diastolic dysfunction (DD) in patients hospitalized with heart failure (HF) with mildly reduced ejection fraction (HFmrEF) in sinus rhythm. - Background - Data regarding the prognostic impact of DD in patients with HFmrEF is limited. - Methods - From 2016 to 2022, all patients hospitalized with HFmrEF (i.e., left ventricular ejection fraction 41-49% and signs and/or symptoms of HF) were retrospectively included at one institution. Patients with DD were compared to patients without (i.e., non-DD), further risk stratification was performed according to the severity of DD. The primary endpoint was all-cause mortality at 30 months (interquartile range (IQR) 15-61 months), key secondary endpoint was rehospitalization for worsening HF. - Results - From a total of 1154 patients (median age 68 years, 68% males) hospitalized with HFmrEF, concomitant DD was present in 72% (grade I: 56%, grade II: 14%, grade III: 2%). Patients with DD were older (71 years vs. 65 years; p = 0.001) and presented with higher rates of cardiovascular comorbidities. The presence of DD was not associated with the risk of long-term all-cause mortality (adjusted HR = 0.815; 95% CI 0.612-1.085; p = 0.161) or HF-related rehospitalization (adjusted HR = 0.736; 95% CI 0.442-1.225; p = 0.238). Furthermore, the outcome did not differ in patients with more advanced stages of DD. - Conclusion - DD is commonly prevalent in patients with HFmrEF, but not associated with long-term prognosis.